Oxidative Stress: A Putative Link Between Lower Urinary Tract Symptoms and Aging and Major Chronic Diseases - Xu, Zhenqun; Elrashidy, Rania A.; Li, Bo; Liu, Guiming (Frontiers in Medicine, 2022)
Aging and major chronic diseases are risk factors for lower urinary tract symptoms (LUTS). On the other hand, oxidative stress (OS) is one of the fundamental mechanisms of aging and the development of chronic diseases. Therefore, OS might be a candidate mechanism linking these two clinical entities. This article aims to summarize the studies on the prevalence of LUTS, the role of OS in aging and chronic diseases, and the potential mechanisms supporting the putative link. A comprehensive literature search was performed to identify recent reports investigating LUTS and OS in major chronic diseases. In addition, studies on the impact of OS on the lower urinary tract, including bladder, urethra, and prostate, were collected and summarized. Many studies showed LUTS are prevalent in aging and major chronic diseases, including obesity, metabolic syndrome, diabetes, cardiovascular disease, hypertension, obstructive sleep apnea, autoimmune diseases, Alzheimer’s disease, and Parkinson’s disease. At the same time, OS is a key component in the pathogenesis of those chronic diseases and conditions. Recent studies also provided evidence that exacerbated OS can cause functional and/or structural changes in the bladder, urethra, and prostate, leading to LUTS. The reviewed data support the concept that OS is involved in multiple risk factors-associated LUTS, although further studies are needed to confirm the causative relationship. The specific ROS/RNS and corresponding reactions/pathways involved in chronic diseases and associated LUTS should be identified in the future and could serve as therapeutic targets.